Endurance exercise in seniors: Tonic, toxin or neither?. (25th May 2020) - Eze‐Nliam, Chete; Schiller, Nelson B.; Hayami, Doug; Ghahghaie, Farzin; Bibby, Dwight; Fang, Qizhi; Marcus, Gregory M.; Åström Aneq, Meriam
Abstract: Introduction: Cardiac adaptation to sustained exercise in the athletes is established. However, exercise‐associated effect on the cardiac function of the elderly has to be elucidated. The aim of this study was to analyse left (LV) and right ventricular (RV) characteristics at different levels of chronic exercise in the senior heart. Materials and methods: We studied 178 participants in the World Senior Games (mean age 68 ± 8 years, 86 were men; 48%). Three groups were defined based on the type and intensity of sports: low‐, moderate‐ and high‐intensity level. Exclusion criteria were coronary artery disease, atrial fibrillation, valvular heart disease or uncontrolled hypertension. LV and RV size and function were evaluated with an echocardiogram. Results: LV trans‐mitral inflow deceleration time decreased in parallel to the intensity of chronic exercise: 242 ± 54 ms in low‐, 221 ± 52 ms in moderate‐ and 215 ± 58 ms in high‐intensity level, p = .03. Left atrial volume index (LAVI) was larger in high‐intensity group, p = .001. The LAVI remained significantly larger when adjusting for age, gender, heart rate, hypertension and diabetes ( p = .002). LV and RV sizes were larger in the high‐intensity group. LV ejection fraction and RV systolic function evaluated by tissue Doppler velocity, atrioventricular plane displacement and strain did not differ between groups. Conclusion: Left ventricular diastolic filling is not only preserved, but may also be enhanced in long‐term, top‐level senior athletes. Moreover, LV and RV systolic function remain unchanged at different levels of exercise. This supports the beneficial effects of endurance exercise participation in senior hearts.